The Palgrave Handbook of Corporate Social Responsibility 2020
DOI: 10.1007/978-3-030-22438-7_25-1
|View full text |Cite
|
Sign up to set email alerts
|

Employee Volunteering

Abstract: Employee volunteering (EV) was introduced as employer-supported volunteering and now also covers employee-led volunteering initiatives. For employers, EV is usually embedded in the company's corporate social responsibility (CSR)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 29 publications
(43 reference statements)
1
1
0
Order By: Relevance
“…The study found evidence of the link between organizational pride and EV, consistent with existing research (Bhinekawati et al, 2020; Booth et al, 2009). However, employees’ interpretations of these sentiments stretch beyond their volunteering experiences, to include reflections on their organization’s broader behavior.…”
Section: Theme 1: Employee Motivations—cause Over Company?supporting
confidence: 90%
See 1 more Smart Citation
“…The study found evidence of the link between organizational pride and EV, consistent with existing research (Bhinekawati et al, 2020; Booth et al, 2009). However, employees’ interpretations of these sentiments stretch beyond their volunteering experiences, to include reflections on their organization’s broader behavior.…”
Section: Theme 1: Employee Motivations—cause Over Company?supporting
confidence: 90%
“…Existing EV research examines its effects on employee behavior but predominantly focuses upon the strategic benefits for the (employer) organization (Booth et al, 2009; Peloza & Hassay, 2006). Research has investigated how EV programs produce outcomes such as increased motivation/morale (Bhinekawati et al, 2020; do Paço & Nave, 2013), retention and attraction of employees (Sanchez-Hernandez & Gallardo-Vázquez, 2013), and increased employee pride/commitment (Jones, 2010; Peloza et al, 2009). Similarly, where research examines employee motivations, the focus is on how volunteering strengthens organizational commitment (Gómez & Fernández, 2017; Haski-Leventhal et al, 2019).…”
Section: Examining Existing Ev Researchmentioning
confidence: 99%